Aset Budaya sebagai Daya Tarik Destinasi Wisata Desa Pujiharjo - Siswo Martono; Mochammad Arifin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The people of Pujiharjo Village have a unique tradition of ancestral heritage and its existence continues to be preserved by posterity until now. These traditions, including: sayan, watering, downloading and picking the sea. This study aims to analyze the traditions that have been passed down from generation to generation and the participation of the cultural conservation community as an effort to promote Pujiharjo Village as a cultural tourism destination. The research method uses descriptive qualitative. The results show that the Sayan tradition is a form of mutual cooperation to ease the burden on the citizens and the tradition is an expression of gratitude for the grace of God Almighty. Community participation is categorized into two groups, namely conservationists and cultural connoisseurs